Antioxidant Activity and Total Flavonoid of Extract of Bark Vitex pinnata L. - Zulfan; Yessi Febriani; Sumardi (Yayasan Penelitian dan Inovasi Sumatera, 2023)
Background: The bark of Vitex pinnata L is not yet optimally utilized, primarily being used in boat construction while the remaining material becomes waste that is either buried or burned in trash. Therefore, it is necessary to explore more efficient and economically valuable uses for the bark of the laban tree. Objective: The aim of this research is to identify the chemical compounds, flavonoid content, and antioxidant activity present in the methanol extract of Vitex pinnata L bark. Method: Phytochemical screening was conducted on the methanol extract of Vitex pinnata L. bark. To obtain the extract, the simplicia powder was macerated using methanol as the solvent. The total flavonoid content and antioxidant activity were then tested using the 1,1-diphenyl-2-picryhydrazil (DPPH) method. Results: the phytochemical screening indicated that the Vitex pinnata L. bark extract contains alkaloids, flavonoids, and tannins. The total flavonoid test yielded 17.27%, and the antioxidant activity test revealed that the methanol extract of the laban tree bark has antioxidant activity with an IC50 value of 43.22 ppm. Conclusion: This extract has strong potential as an antioxidant agent.